How to improve efficiency in cancer care: Dimensions, methods, and areas of evaluation. (December 2022) - Ferrara, Lucia; Otto, Monica; Aapro, Matti; Albreht, Tit; Jonsson, Bengt; Oberst, Simon; Oliver, Kathy; Pisani, Eduardo; Presti, Pietro; Rubio, Isabel T.; Terkola, Robert; Tarricone, Rosanna
Abstract: Efficiency in healthcare is crucial since available resources are scarce, and the cost of inefficient allocation is measured in prior outcomes. This is particularly relevant for cancer. The aim of this paper is to gain a comprehensive overview of the areas and dimensions to improve efficiency, and establish the indicators, different methods, perspectives, and areas of evaluation, to provide recommendations for how to improve efficiency and measure gains in cancer care. Methods: We conducted a two-phase design. First, a comprehensive scoping literature review was conducted, searching four databases. Studies published between 2000 and 2021 were included if they described experiences and cases of efficiency in cancer care or methods to evaluate efficiency. The results of the literature review were then discussed during two rounds of online consultation with a panel of 15 external experts invited to provide insight and comments to deliberate policy recommendations. Results: 46 papers met the inclusion criteria. Based on the papers retrieved we identified six areas for achieving efficiency gains throughout the entire care pathway and, for each area of efficiency, we categorized the methods and outcomes used to measure efficiency gain. Conclusion: This is the first attempt to systemize a scattered body of literature on how to improve efficiency in cancer care and identify key areas of improvement. Policy summary: There are many opportunities to improve efficiency in cancer care. We defined seven policy recommendations on how to improve efficiency in cancer care throughout the care pathway and how to improve the measurement of efficiency gains. Highlights: There are many opportunities to improve efficiency in cancer care. We have identified key areas for achieving efficiency gains across the care pathway. We have categorized the outcome used to measure efficiency gains. Stakeholders should come together to agree on minimum core input and outcomes. Appropriate measures should include accurate holistic cost measurement models.